SELLING CANANG SARI (As an Alternative of Effort in Informal Sector to overcome household economics problem) - Desak Putu Eka Nilakusmawati (PIRAMIDA, 2007)
Decrease in family income represent an impact of economic pressures, as an effect of economic crisis. Other side, the existing problems that extension of the job opportunity in the urban area with existence of development in the various sector do not absorb entire labour force which is progressively growing larger its amount.Economic problem force woman of lower economic class to involved take part in earning for increase family income by working beyond domestic sectors. Involvement of woman in labor market trigered by family’s economic problems, besides existence of the job opportunity factor. Alternative effort being carried out is by selling canang.Increasing of urban community activities in Denpasar City makes them have no time to make banten or canang. To find an easier way to overcome this situation, many people tend to buy canang/banten which is ready to use, also more practical and spent less time than the time spent when they make by themselves . This phenomenon gives a chance to canang sellers to get income additional. In the difficult condition of the economics problem, many woman have to take part to overcome economic problems which they face. One of the alternative is involved into labour market, and involve in trade is one of the choice. Because of the existence of opportunity as explained above, many women overcome their economic problems and try to give contribution to their family income by selling the canang.Phenomenon more and more canang sellers which are spread alongside the road side in Denpasar City shown that the informal sector have a great role to maintaining and also improving household economics. The effort as the canang seller can represent an alternative of effort in informal sector to overcome economics problem in the household level. Roles of woman as a subject of this informal sector, have a big contribution in maintaining household economics.